Nitrification in the Contact-Stabilization Process - Wisjnuprapto Wisjnuprapto; S. Saipanich; B. Capdeville; H. Roques (Journal of Mathematical and Fundamental Sciences, 1982)
Abstract. A series of experiment on the contact-stabilization process treating municipal waste water were conducted at various sludge ages. Sludge recycling rates, hydraulic retention times in contact-stabilization reactors, and at constant temperature. A kinetic model of nitrifiers growth rates in the contact reactor were developed based on the calculated values of the experimental results, as a function of sludge age and fractional biomass in the contact reactor. The influence of these parameters on the nitrification efficiency were observed during the experiments; the ammonia removal rate as a function of the VSS and ammonia nitrogen consumption by the microorganisms were determined experimentally.Sari. Telah dilakukan satu seri percobaan pengolahan air buangan kota dengan menggunakan proses kontak-stabilisasi pada berbagai variasi harga umur sludge, sludge recycling rate, waktu retensi di dalam reaktor kontak dan reaktor stabilisasi, pada temperatur konstan. Berdasarkan nilai yang diperhitungkan dari hasil percobaan, telah dicoba untuk mengembangkan sebuah model kinetik tentang kecepatan pertumbuhan bakteri nitrifikasi (nitrifier) di dalam reaktor kontak sebagai fungsi dari umur sludge dan fraksi biomas di dalam kontak reaktor. Selanjutnya, dalam percobaan ini juga diamati pengaruh parameter-parameter tersebut lerhadap efisiensi nitrifikasi. Dan dari hasil percobaan juga telah dihitung kecepatan penghilangan ammonia sebagai fungsi dari Volatile Suspended Solids yang terbentuk dan pemakaian nitrogenammonia oleh mikroorganisme.